Model forensic science. Issue 5 (2nd September 2016) - Edmond, Gary; Found, Bryan; Martire, Kristy; Ballantyne, Kaye; Hamer, David; Searston, Rachel; Thompson, Matthew; Cunliffe, Emma; Kemp, Richard; San Roque, Mehera; Tangen, Jason; Dioso-Villa, Rachel; et al.
Abstract : This article provides an explanation of the duties and responsibilities owed by forensic practitioners (and other expert witnesses) when preparing for and presenting evidence in criminal proceedings. It is written in the shadow of reports by the National Academy of Sciences (US), the National Institute of Standards and Technology (US), the Scottish Fingerprint Inquiry and a recent publication entitled 'How to cross-examine forensic scientists: A guide for Lawyers'. The article examines potential responses to questions focused on the need for scientific research, validation, uncertainties, limitations and error, contextual bias and the way expert opinions are expressed in reports and oral testimony. Responses and the discussion is developed around thematics such as disclosure, transparency, epistemic modesty and impartiality derived from modern admissibility and procedure rules, codes of conduct, ethical and professional responsibilities and employment contracts. The article explains why forensic practitioners must respond to the rules and expectations of adversarial legal institutions. Simultaneously, in line with accusatorial principles, it suggests that forensic practitioners employed by the state ought to conduct themselves as model forensic scientists .